2000
DOI: 10.1038/sj.cgt.7700109
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus infection induces B7-1/B7-2-independent T-cell costimulatory activity in human melanoma cells

Abstract: Viral oncolysates of Newcastle disease virus (NDV) have been widely used for the treatment of malignant melanoma. Apparently, this nononcogenic and apathogenic paramyxovirus can alter the immunogenicity of tumor cells. To determine the influence of NDV infection on a tumor-specific T-cell response on a functional level, we used autologous primary melanoma cells infected with the NDV-strain Ulster. Therefore, melanoma cells and tumor-infiltrating lymphocytes were prepared from a freshly resected tumor, and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
2
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 34 publications
1
54
2
2
Order By: Relevance
“…However, it was demonstrated that HN molecules when expressed at the surface of NDV-infected tumor vaccine induce a B7-1/B7-2-independent costimulation effect leading to induction of CD28RC in T lymphocytes (23,47). These observations differ from the present results obtained with naive T-cells in so far as Termeer et al (47) and Ertel et al (23) used, in their studies, memory T cells.…”
Section: Discussioncontrasting
confidence: 83%
“…However, it was demonstrated that HN molecules when expressed at the surface of NDV-infected tumor vaccine induce a B7-1/B7-2-independent costimulation effect leading to induction of CD28RC in T lymphocytes (23,47). These observations differ from the present results obtained with naive T-cells in so far as Termeer et al (47) and Ertel et al (23) used, in their studies, memory T cells.…”
Section: Discussioncontrasting
confidence: 83%
“…It also possibly prevents activation-induced cell death (AICD) or unresponsiveness. 9 The IFN-a detected in our stimulation cultures 10 appears to be of particular significance because type I interferons were recently shown to function like ''danger signals'' for DCs, causing their activation and promoting cross-priming of CD8 T cells. 31 For many of these reasons, the polyclonal T-cell response to the modified tumor vaccine appears to be unusually effective.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4][5] These Phase I/II studies included primary operated breast carcinoma, 1 glioblastoma 3 and squamous cell carcinoma of the head and neck (HNSCC). 4 Infection of tumor cells with Newcastle Disease Virus (NDV) was shown to introduce into the tumor cells danger signals 6 by way of double-stranded RNA 7,8 and T-cell costimulatory activity 9 via the viral cell surface-expressed hemagglutinin-neuraminidase (HN) protein. 10 NDV can infect tumor cells efficiently, leading to high levels of HN expression on proliferating and nonproliferating cells because it replicates in the cytoplasm and does not integrate into the DNA.…”
mentioning
confidence: 99%
“…In the past, we have been working with lentogenic strains such as Ulster and LaSota to infect patient derived tumor cells ex vivo for production of the immunogenic virus modified autologous tumor vaccine, ATV-NDV. We studied the immunological effects of this tumor-cell modification (28)(29)(30)(31) In the present study, we investigated systemic tumor targeting of NDV and used for this purpose either a recombinant mesogenic strain derived from LaSota (NDFL) or the native velogenic strain Italien. Both strains have a furin cleavage site in their F protein which allows its activation in a proteolytic environment such as the tumor microenvironment (25,36).…”
Section: Discussionmentioning
confidence: 99%